Genetic variability and inheritance of aluminum toxicity tolerance in oat - Sánchez-Chacón, Carlos Danilo; Federizzi, Luiz Carlos; Milach, Sandra Cristina Kothe; Pacheco, Marcelo Teixeira (Pesquisa Agropecuaria Brasileira, 2000)
Twenty-one oat (Avena sativa L.) genotypes from the Universidade Federal do Rio Grande do Sul breeding program, in Brazil, were evaluated for their reaction to aluminum (Al) toxic levels in nutrient solutions. The Al levels tested were 5, 10, 15, 20 and 30 g kJ-1. The root regrowth was evaluated after 48 hours in presence of Al. Phenotypic variability was observed at 10 g kJ-1 and upper levels. Two groups were clearly distinguished at 20 g kJ-1 level, one of tolerant and the other of sensitive genotypes. The genetic bases of Al tolerance were determined on P1, P2, F1 and F2 generations of nine crosses among tolerant x sensitive genotypes. The tolerant response was conditioned by one gene with dominant effect. The wide sense heritability was intermediate to high, allowing selection of tolerant genotypes in early generations, followed by progeny test to identify homozygous lines. The results of this study suggest that the hydroponic method is reliable for screening germplasm to Al toxicity and may be used in the routine of oat breeding programs.